The comparative analysis of the factor structure of sociability in groups of successful and unsuccessful L2 Learning individuals - G V Zarembo (Peoples' Friendship University of Russia (RUDN University), 2009)
The article presents the profound comparative analyses of the factor structure of sociability. The results in groups of successful and unsuccessful L2 learning individuals are given. The structure of sociability as an individual characteristic of the learner is presented.